Efeitos da cyber vitimização na saúde mental: um estudo comparativo entre não heterossexuais e heterossexuais - Morais, Mísia Carolyne Pereira de (2022)
Cyberbullying is the term that has been used to characterize intentional and harmful aggression that occurs through the exchange of electronic information. This type of violence is usually directed at people or groups that belong to some type of minority, and can cause damage to the victims' mental health. The present dissertation aimed, based on the Minority Stress Theory, to investigate possible relationships between cyber victimization, sexual minorities and mental health. A systematic review of the literature was carried out in the search for variables that could act within the relationship between these three constructs, as mediators or moderators. Based on the results of the review, hypotheses were created for two empirical studies. The first study was carried out with 256 participants, with a mean age of 25.92 years (SD = 5.19), and the second, with 254 participants with a mean age of 27.56 years (SD = 7.56). They excelled in understanding the relationship between cyber victimization and mental health, respectively: (1) the role of self-efficacy in physical activity and social support; and (2) smartphone addiction and frequency of substance use. In both, differences between heterosexuals and non-heterosexuals were analyzed. Moderation and mediation analyzes did not show significant results. On the other hand, in the first empirical study, a one-way ANOVA indicated higher rates of anxiety among those belonging to the LGBTQIAP+ group [F (1.254) = 7.08; p = 0.01; η2 = 0.03]. The second study draws attention to the fact that, in general, the LGBTQIAP+ group consumes, to a greater extent, both alcohol, tobacco and marijuana. Emphasis on tobacco [t (254) = 3.90; p = 0.00]. In view of its complexity and actuality, further studies on the subject are necessary.